Gente que cuida de gente: a trajetória de Wanda Horta na arte e ciência do cuidado (1926-1981) - Goulart, Vanessa Alves (2020)
The analysis of the trajectory of one of the main nurses responsible for the dissemination and recognition of the art and science of care in Brazil is the central objective of this research. A scholar and a poet, Wanda Horta (1926-1981) was an Emeritus Professor of the Nursing School at the University of São Paulo, the institution where she worked for over twenty years and stood out for promoting works that focused on demonstrating the scientific and autonomous character of Nursing as a field of knowledge, as well as fighting for the humanization of care, so that Nursing could be acknowledged as people taking care of people, with their potential and despondency. Furthermore, Horta founded the magazine Nursing in New Dimensions, which circulated between 1975 and 1979 and had a space dedicated to the publication of poetry, that allowed the readers to understand poetry as a form of care. The perspective of this study is to highlight the role of women in the construction of the care field and to value their experiences as fundamental characters in historical narratives. Therefore, the study seeks to map the existing sources that bring up information about Horta's trajectory in order to answer what were the experiences lived by this author as a woman working in the field of care. What historical and social processes were behind the notable concerns in Horta's writings, especially regarding the resistance to the scientific recognition of Nursing in her time? How traditional historical narratives address the role of women in the development of the health practices and knowledge necessary for our survival, and how Horta's work, as well as her productions, is connected to this phenomenon? Why did the author consider the Nurse-Being as people who take care of people? Based on what understanding can we interpret the practice of publishing poetry inaugurated by Horta in the magazine Nursing in New Dimensions? The research was conducted methodologically using the theoretical assumptions presented by the Social History of Women, Oral History and Trajectory Studies. The analyzed sources comprise records and unpublished data, such as three interviews we conducted and the collection of private documents by Wanda Horta, which is currently under the management of the Science, Health, Gender and Feeling Research Group - CISGES/ UNISA/CNPq, from Santo Amaro University. The copies of the magazine Nursing in New Dimensions being preserved at the Wanda de Aguiar Horta of the Nursing School Library of the University of São Paulo were also consulted, as well as the books Processo de Enfermagem (1979) and Doação (1983), and some scientific articles the author has published throughout her career